The extreme 2016 wheat yield failure in France - Nóia Júnior, Rogério de S.; Deswarte, Jean‐Charles; Cohan, Jean‐Pierre; Martre, Pierre; Velde, Marijn; Lecerf, Remi; Webber, Heidi; Ewert, Frank; Ruane, Alex C.; Slafer, Gustavo A.; Asseng, Senthold (Global change biology, 2023)
France suffered, in 2016, the most extreme wheat yield decline in recent history, with some districts losing 55% yield. To attribute causes, we combined the largest coherent detailed wheat field experimental dataset with statistical and crop model techniques, climate information, and yield physiology. The 2016 yield was composed of up to 40% fewer grains that were up to 30% lighter than expected across eight research stations in France. The flowering stage was affected by prolonged cloud cover and heavy rainfall when 31% of the loss in grain yield was incurred from reduced solar radiation and 19% from floret damage. Grain filling was also affected as 26% of grain yield loss was caused by soil anoxia, 11% by fungal foliar diseases, and 10% by ear blight. Compounding climate effects caused the extreme yield decline. The likelihood of these compound factors recurring under future climate change is estimated to change with a higher frequency of extremely low wheat yields.